Differential gene expression profiles in the hippocampus of senescence-accelerated mouse - Cheng, X.; Zhou, W.; Zhang, Y.; Zhou, D.; Yang, R.; Chen, L.
The senescence-accelerated mouse (SAM)is an animal model for studying senescence and age-associated disorders due to its inherited aging phenotype. The SAM/prone8 (SAMP8)is a useful animal model to investigate the fundamental mechanisms involved in age-related learning and memory deficits that may have relevance to age-associated AD, while SAM/resistant1 (SAMR1)shows normal. To identify genes rendering the cognitive deterioration with aging, the subtractive cDNA libraries containing 1924 clones with the positive ratio of 96.18
Keywords: SENESCENCE-ACCELERATED MOUSE; ALZHEIMER'S DISEASE; CDNA MICROARRAY